Pancasila sebagai ideologi negara dan pemersatu bangsa Indonesia - Baihaqi, Khalif (Maliki Interdisciplinary Journal, 2023)
Pancasila is the ideological foundation of the Indonesian state, which has played an important role in maintaining the integrity and unity of the nation. This concept is not only a philosophical basis, but also a bond that unites various religions, ethnicities and cultures in Indonesia. Pancasila is clearly the philosophy of the Indonesian state. The priceless gift given by God Almighty to the Indonesian nation is Pancasila. The ideology and one of the foundations that unites the Indonesian nation is Pancasila and is one. Indonesian civilization is built on Pancasila.